Overexpression of syndecan-4 inhibits myogenesis by regulating the expression of myogenic regulatory factors - Sarang Choi; Jeong-Woong Park; Sang In Lee; Sangsu Shin (Journal of Animal Science and Technology)
Syndecan-4, a type of heparin sulfate proteoglycan, plays an important role in muscle development, regeneration, and maintenance. Although, the important effects of syndecan-4 on the regulation of myogenesis in mice, turkeys, and bovines have been consistently reported, the molecular mechanisms of syndecan-4 in myogenesis are not well understood. In this study, the role of syndecan-4 in regulating myogenesis was investigated in quail myoblas (QM7) cells, which constitute a quail myogenic cell line. Overexpression of syndecan-4 inhibited myogenesis, resulting in reduced myoblast fusion and shorter myotubes than in the control group. Therefore, the cells overexpressing syndecan-4 showed a smaller total myotube area than did the control cells. Furthermore, these cells had lesser myosin heavy chain proteins, suggesting that muscle differentiation is inhibited by syndecan-4. To investigate the inhibitory effect of syndecan-4 on myogenic differentiation, the mRNA expression levels in several genes known to regulate myoblast proliferation and differentiation were compared. Myogenic regulatory factors, including myogenic factor 5, myogenic differentiation 1, and myogenin, showed significantly different expressions between the groups during myogenesis. Myostatin, a negative regulator of muscle growth, showed significantly higher expression on day 4 in cells overexpressing syndecan-4. In conclusion, syndecan-4 could delay and inhibit muscle differentiation by regulating the expression levels of myogenic factors and muscle growth regulator in quail myocytes. This study provides valuable information regarding the role of syndecan-4 in myogenesis, which may aid in improving the production of poultry meat.